4 Effects on Hospital Admissions from the Completion of Good Quality Treatment Escalation Plans in Care Homes. (6th February 2020) - Courtney, E; Pollock, L; Gagg, C; Stevenson, H; Male, S
Abstract: Topic: Some care home residents are admitted to hospital when they either do not wish for admission or will not benefit from admission. Meeting residents and their next of kin to explore the person's goals and priorities can facilitate the completion of a good quality Treatment Escalation Plan (TEP). Intervention: A pilot service was commenced in November 2018 to complete and review TEPs in the top ten admitting care homes to Musgrove Park Hospital. A small team of clinicians (1.5 full time equivalent) worked in the selected care homes completing and reviewing TEPs, with an aim to see 80% of residents. Clinicians met residents and their next of kin to discuss the person's wishes. Completed TEPs were left in the care home, shared with GPs and uploaded to the IT system in the acute hospital. The number of Emergency Department (ED) attendances and inpatient admissions from care homes were recorded and compared to data from 2017/18. Improvement: Over 5 months, 492 residents had TEPs reviewed or completed by the team; this was 76% of the total bed base of the selected care homes. Data were compared to the same period a year earlier. During the final two months of the pilot, attendances to ED from care homes with the intervention were reduced by 24%, whilst the control group saw an 8% decrease. In the same period, inpatient admissions from the intervention group were reduced by 35%, compared to an 11% decrease in the control care homes. Discussion: Whilst there are too few data to provide conclusive evidence, early indications suggest that facilitating the discussion of good quality TEPs in care homes reduces attendances to ED and inpatient admissions. Further evaluation is required as the service continues. There were challenges to the implementation of the pilot; these included communication and engagement with GPs, in addition to access to GP IT systems.